2017
DOI: 10.5709/ce.1897-9254.236
|View full text |Cite
|
Sign up to set email alerts
|

Market reactions to dividends announcements and payouts. Empirical evidence from the Warsaw Stock Exchange

Abstract: The results obtained for the average cumulative abnormal returns corroborate the findings reached for the average cross-sectional abnormal returns in the case of the first dividend and dividend increase subsamples. However, the average cross-sectional abnormal returns calculated within the eleven-day-long event window around the dividend payment day turn out to be statistically insignificant. The obtained results provide evidence that the Polish stock market reaction to dividend announcements is positive and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…The connection between unchanged dividend and stock price is statistically insignificant. Mrzygłód and Nowak (2017) investigated how prices on the Polish stock market react to dividend announcements and dividend payouts made by companies listed on the Warsaw Stock Exchange.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The connection between unchanged dividend and stock price is statistically insignificant. Mrzygłód and Nowak (2017) investigated how prices on the Polish stock market react to dividend announcements and dividend payouts made by companies listed on the Warsaw Stock Exchange.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2018; Anwar et al. , 2016; Mrzygłód and Nowak, 2017; Ross, 1977). Recent research also provides for a positive influence of these corporate actions.…”
Section: Introductionmentioning
confidence: 99%
“…Ross, 1977;Walter, 1963) arguing that an increase in dividend leads to an increase in share price because it is a signal from the firm managers that the business has sufficient earnings and good prospects. The share price will be negatively affected by dividend cuts and omissions (Al-Shattarat et al, 2018;Anwar et al, 2016;Mrzygł od and Nowak, 2017;Ross, 1977). Recent research also provides for a positive influence of these corporate actions.…”
Section: Introductionmentioning
confidence: 99%
“…Akbar and Baig (2010) find insignificant excess returns for announcements related to cash dividend in their study on Pakistan Stock Market. Mrzygłód and Nowak (2017) conduct a study on the Warsaw Stock Exchange, Poland and found narrow support for the dividend signaling theory for both increase and decrease in the dividend. A positive relationship has been found in the study conducted on Indian stocks listed on the National Stock Exchange (Kumar, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%